2021
DOI: 10.1177/00033197211010602
|View full text |Cite
|
Sign up to set email alerts
|

The Association of a PRECISE-DAPT Score With No-Reflow in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: This study aimed to evaluate the association of admission PREdicting bleeding Complications In patients undergoing Stent implantation and subsEquent Dual Anti Platelet Therapy (PRECISE-DAPT) score with the development of no-reflow (NR) in patients with ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI). In this observational, retrospective study, 335 consecutive STEMI patients who were treated with primary PCI were included. We classified the study populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Recently, a retrospective analysis of 905 patients with STEMI revealed that the incidence of no-reflow was 22.7%. 36 Our result was compatible with this study.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a retrospective analysis of 905 patients with STEMI revealed that the incidence of no-reflow was 22.7%. 36 Our result was compatible with this study.…”
Section: Discussionsupporting
confidence: 93%
“…Since clinical features and event rates were similar to other reports, 8,9,[15][16][17]23,24 we believe that our results might be representative and useful in clinical practice beyond the single-center studies previously reported. 16,[25][26][27][28][29][30] Early risk stratification and structured discharge planning of STEMI patients have gained interest in the last years 12,13 and, moreover, through the COVID-19 pandemic. 6 Adoption of this treatment strategy could reduce hospital costs, resource utilization, and enhance patient satisfaction without affecting outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary no-re ow is a particular complication that should be wacth out in PCI treatment [5] . Nore ow inhibits ow exchange in the myocardial ischemic zone, prevents healing of the myocardial necrotic zone, delays ventricular remodeling, increases the incidence of heart failure [6] , and is an independent predictor of rehospitalization, malignant arrhythmias, and heart failure, recurrent myocardial infarction, and cardiovascular death in patients after PCI [7] .…”
Section: Discussionmentioning
confidence: 99%
“…(3) Underwent PCI, including drug-eluting stenting, bioresorbable stenting, coronary drug balloon dilatation. (4) No-re ow during PCI, de ned as coronary ow TIMI grade 0-2 after coronary balloon dilation or coronary stenting [4] . Exclusion criteria: those with impaired antegrade coronary artery ow due to in situ thrombosis,dissection, severe spasm, and distal embolism.This approach had hospital ethics committee approval and patient ' s informed consent.…”
Section: Study Populationmentioning
confidence: 99%